2018
DOI: 10.1016/j.sjbs.2016.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic activity of the hydroalcoholic extract of leaves of Annona muricata Linnaeus in mice

Abstract: Linnaeus, popularly known as "graviola" and also called soursop, is a species typical of countries with a tropical climate, and it is used in folk medicine as an anticancer, analgesic and antispasmodic agent. The aim of the present study was to validate the gastroprotective activity of the hydroalcoholic extract of the leaves of (HEAM) and to investigate the underlying mechanisms of action for this effect. Gastric lesions were induced in mice by absolute ethanol, acidified ethanol or indomethacin. Before, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…One animal study utilised ethanolic leaf extract at a dose of 25–100 mg/kg demonstrated sedative, anxiolytic and anticonvulsant‐like effect . Antiulcerative ( n = 3) effects of A. muricata hydroalcoholic, ethanolic and ethyl acetate leaf extracts were identified when administered orally over the dose range of 10–400 mg/kg. Of the three studies which investigated A. muricata leaf extract in renal effect, two studies demonstrated a nephroprotective effect, while one demonstrated a nephrotoxic effect with no substantial differences in the dose, formulation or route of administration.…”
Section: Resultsmentioning
confidence: 99%
“…One animal study utilised ethanolic leaf extract at a dose of 25–100 mg/kg demonstrated sedative, anxiolytic and anticonvulsant‐like effect . Antiulcerative ( n = 3) effects of A. muricata hydroalcoholic, ethanolic and ethyl acetate leaf extracts were identified when administered orally over the dose range of 10–400 mg/kg. Of the three studies which investigated A. muricata leaf extract in renal effect, two studies demonstrated a nephroprotective effect, while one demonstrated a nephrotoxic effect with no substantial differences in the dose, formulation or route of administration.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the anti-inflammatory and anticancer properties, the leaves of A. muricata have also been thoroughly investigated for other pharmacological and biological properties. Bento et al revealed that the A. muricata leaves showed significant antiulcer activity against lesions (Bento et al, 2016 ). Besides that, a remarkable wound healing properties by the ethyl acetate leaf extract of A. muricata has been discovered by Moghadamtousi et al ( 2015b ).…”
Section: Other Biological Activities Of Annona Muricata mentioning
confidence: 99%
“…Studies about plants from the Brazilian Cerrado has increased considerably. These plants include graviola ( Annona muricata Linnaeus), which has displayed anti-ulcerogenic effects [ 24 ], bocaiuva ( Acrocomia aculeata ) which has presented anti-diabetic properties [ 25 ] and anti-inflammatory and diuretic actions [ 26 ], and baru ( Dipteryxalata Vog. ), which was observed to cause improvement in lipid profiles and atherogenic indexes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%